“The Wonderful Wizard of OZ”: Building students’ character in ELT through Fantasy Novel - Yustika, Leilya Sari; Mustofa, Ali (English Department, Faculty of Humanities, Andalas University, 2022)
Fantasy is the one of genre in children's literature that is famous all over the world. However, because of the story that tells about imaginary world, the appearance is not quite considered in ELT classroom especially in building students' character. Therefore, this study was conducted to see character education represented in a fantasy novel that is suggested in curriculum 2013 for ELT in Indonesia. The fantasy novel used in this study was The Wonderful Wizard of OZ written by L. Frank Baum. Every condition and situation faced by the character in every plot of story was analyzed using content analysis. The finding showed that fantasy novel could promote character building through the story by showing it in character's attitude in facing a situation or problem. So, even though it told about imaginary world, but it was closed to real life and great as a source for learning.